Deteksi Dini Siswa Korban Bullying dalam Penerapan Data Mining Menggunakan Algoritma C4.5 pada SMP IDN Jonggol - Dadang Iskandar Mulyana; Muhammad Hafiz Siregar (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This research discusses the application of data mining using the C4.5 algorithm for early detection of student victims of bullying at IDN Jonggol Junior High School. The problem studied is how to identify students who are victims of bullying quickly and accurately using the available data analysis. The expected solution is the development of an early detection system that can provide early warning to the school so that intervention can be done earlier. The object of the study was IDN Jonggol Junior High School students. The method used involves collecting demographic data, behavior records, and bullying reports, which are then analyzed using the C4.5 Algorithm. The results showed that the C4.5 algorithm was able to classify student victims of bullying with an accuracy of 78.6%. Preliminary conclusions show that the C4.5 Algorithm has great potential to be used in the early detection of bullying. The implication of this research is the improvement of student safety and well-being through faster and more appropriate intervention. Recommendations from this research are further development of the detection system and its application in other schools